First experience of implementing residency programs at Kazan State Medical University - A. N. Maksudova; A. V. Kosterina; S. V. Kuzmina; N. G. Shamsutdinova; D. I. Abdulganieva; K. Kayumi; A. S. Sozinov (Кардиоваскулярная терапия и профилактика, 2022)
Kazan State Medical University is one of the oldest medical universities in Russia, which has extensive experience in the international education market. The publication describes the features of postgraduate training of residents, first implemented on the basis of Kazan State Medical University in cooperation with the Royal College of Physicians and Surgeons of Canada. The experience of introducing a competency-based educational approach into the residency program according to the CanMEDS system is described. Each competency underlying the CanMEDS principles is considered in detail.